Development of physical process for quinoa fractionation and targeted separation of germ with physical, chemical and SEM studies. (April 2021) - Ray, Amrita; Inamdar, Aashitosh A.; Sakhare, Suresh D.; Srivastava, Alok Kumar
Abstract: Dry milling process is developed, which is scalable to industrial capacity and more eco-friendly compared to wet method for separation of germ, perisperm and bran fractions from quinoa as potential functional food ingredients. Peripheral germ is the most important functional component of grain as it stores most of the protein and fat reserve. Fractionation of the grain is performed at different conditioning moisture (viz., 12, 14, 16, 18 & 20%). Medium conditioning moisture (14–16%) has shown optimum balance between yield and quality of the fractions; and has been explored further to develop a novel process specifically targeted for germ separation by making significant changes in the flow diagram of the roller milling process. This developed process enables separation of germ with recovery of 82.57% of protein, 80.04% fat and 81.20% of minerals with respect to germ extracted manually. Bran obtained by the developed novel process shows double the amount of dietary fibre compared to quinoa seed; perisperm having <1% mineral content with brightness in colour portrays purity of the fraction. Isolated fraction of quinoa germ has high content of protein, ash and fat. Separated fractions with higher nutritional value have numerous functional applications in food industry. Highlights: Effect of moisture conditioning on quinoa roller milling was studied for fractionation. Conditioning moisture (14–16%) has shown optimum balance between yield and quality. Further, process was improved for germ separation by making significant changes in the flow diagram. Developed process separated quinoa germ with recovery of >84% yield and >80% purity. Fractions with higher nutritional value have numerous functional applications.